The Moisture Content of Robusta Coffee Beans is dried in the Sun and the Room Temperature is measured with a Microcontroller-based Moisture Content Analyzer - Tompunu, Alan Novi; Hafizhah, Tamara; Handayani, Marta Tika (International Journal of Research in Vocational Studies (IJRVOCAS), 2024)
The water content of coffee beans plays an important role in the coffee industry. The water content of fresh coffee beans is still high so it needs to be reduced to meet the SNI standard or around 11-12%. Reducing the water content of coffee beans can be done by drying them in the sun and at room temperature. There is no tool made to measure the water content of coffee beans. This study created a microcontroller-based coffee bean water content measuring tool. Measurements were made on robusta coffee beans. Water content measurements were carried out on coffee beans that were dried in the sun for three days and at room temperature for seven days. Water content measurements were also carried out using the AR991 water content measuring tool as a comparison. From the results of measurements using a microcontroller-based water content measuring tool, it was found that the water content of coffee beans dried in the sun decreased day by day starting from 23% on the first day and 10% on the third day. From the AR991 water content measuring tool, it was found that the water content of coffee beans was 23.3% on the first day and 11.9% on the last day. The moisture content of coffee beans dried at room temperature has a moisture content of 22% on the first day and 11% on the last day using a microcontroller-based moisture meter. While the results of measuring the moisture content of coffee beans using the AR991 moisture meter are 23.3% on the first day and 12% on the last day.